The Judiciary of China: Understanding its Independence, Glitches and Reforms Measures - Mohammad Saiful Islam; Abdul Malek; Masoud Ahmad; Anjuman Ara Begum (Mediterranean Journal of Social Sciences, 2022)
The judiciary of china and its degree of independence is the vital theme of intellectual discourse not only among the western jurists but also among Chinese intellect as the judiciary of China is randomly criticized by the westerns for not upholding the actual independence. In fact, the Chinese authority never explores concentration to admit and implement the western concept of the independent judiciary rather they have attempted to build a strong and independent adjudication system with unique Chinese characteristics. Hence, the Chinese Communist Party (CCP) has declared and implemented various reforms initiative and plays a momentous role to execute all reforms plan properly. This paper, largely, endeavors to address the understanding of judicial independence in China, ascertaining its glitches and deficiencies with the scheme of various rounds of reform policy as an extent of strengthening the impartial and independent adjudication system. The study finds that the competent authority devotes vast judicial reform agenda to improving the court management, appointing qualified judges through the comprehensive selection process, to eliminate internal interference from courts seniors and political leaders. Received: 26 June 2022 / Accepted: 28 August 2022 / Published: 2 September 2022